Antimicrobial resistance in urine and skin isolates in Timor-Leste. (June 2018) - Marr, Ian; Sarmento, Nevio; O'Brien, Matt; Lee, Karl; Gusmao, Celia; de Castro, Gloria; Janson, Sonja; Tong, Steven Y.C.; Baird, Rob W.; Francis, Joshua R.
Highlights: Timor-Leste (SE Asia) has few microbiological services and minimal knowledge of in-country antimicrobial resistance rates. Prospective urine and skin isolates were collected from the national hospital in Dili. 35% of Enterobacteriaceae were ceftriaxone-resistant and 11% of S. aureus were CA-MRSA; no carbapenem was resistance found. ESBL rates were consistent with surrounding regional data, but MRSA rates were lower than expected. This study allows new treatment guidelines for clearer empirical treatment and rationalisation of current antibiotic use. Abstract: Objectives: High rates of antimicrobial resistance (AMR) are seen throughout Southeast Asia. However, limited AMR data exist for Timor-Leste, which is situated on the south-eastern portion of the Malay Archipelago. The purpose of this study was to identify AMR in bacteria isolated from urine and skin swabs from patients in Dili, the capital of Timor-Leste. Methods: Urine and skin swabs were collected from symptomatic patients in Timor-Leste and were processed for bacterial culture. Isolates were processed in Australia using a VITEK ® 2 system for bacterial identification and to determine antimicrobial susceptibility according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: A total of 154 urine isolates and 57 skin isolates were analysed. Of the Enterobacteriaceae, 35% were resistant to ceftriaxone with an extended-spectrum β-lactamase (ESBL)-producing phenotype. Carbapenem resistance was not observed in any of the Gram-negative isolates. Of the Staphylococcus aureus isolates, 11% were of the community-associated methicillin-resistant S. aureus (CA-MRSA) phenotype. Conclusions: A moderately high proportion of Gram-negative urine isolates in Timor-Leste demonstrate phenotypic ESBL production, and a relatively low proportion of S. aureus isolates were methicillin-resistant. Improved understanding of AMR rates in Timor-Leste can help guide antimicrobial prescribing and inform antimicrobial stewardship strategies.